Olopatadine hydrochloride ophthalmic solution for the treatment of allergic conjunctivitis. (24th July 2017) - Gonzalez-Estrada, Alexei; Reddy, Keerthi; Dimov, Ves; Eidelman, Frank
ABSTRACT: Introduction : Olopatadine hydrochloride is an antihistamine and mast cell stabilizer available as oral, intranasal and ocular preparations. Most of the practical applications of olopatadine therapy focus on the treatment of allergic rhinoconjunctivitis via intranasal and ocular routes. Areas covered : This article was created from a comprehensive literature search with information taken from meta-analyses, systematic reviews, and clinical trials of children and adults. The articles that have been selected, evaluate the use of intranasal and ocular antihistamines and their role in allergic rhinoconjunctivitis. Expert opinion : Olopatadine is significantly more effective than placebos in relieving the symptoms of allergic rhinoconjunctivitis. It can function both as a viable alternative or addition to first line therapies such as intranasal steroids and oral antihistamines.